2016
DOI: 10.1097/mbc.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume is related with ischemic stroke in patients with sinus rhythm

Abstract: Stroke is the leading cause of disability worldwide. It is known that atrial fibrillation and left atrial enlargement contribute ischemic stroke, and mean platelet volume (MPV) increases in patients with ischemic stroke and atrial fibrillation. We aimed to determine whether higher MPV is associated with ischemic stroke in patients with sinus rhythm. We evaluated 74 patients in sinus rhythm and with ischemic stroke (Group 1) and 90 age-matched and sex-matched healthy individuals as control group (Group 2). Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Interestingly, a higher MPV value has also been associated with acute ischemic stroke in patients with sinus rhythm and without heart failure or left atrial enlargement [9], whereas a lower MPV value was proven to be a reliable biomarker for the screening of brain injury in patients with mild head trauma [10].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a higher MPV value has also been associated with acute ischemic stroke in patients with sinus rhythm and without heart failure or left atrial enlargement [9], whereas a lower MPV value was proven to be a reliable biomarker for the screening of brain injury in patients with mild head trauma [10].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies showed that patients with AS had higher PC than controls [24,35,36]. Eleven studies demonstrated lower PC in the patient group [12][13][14]23,[25][26][27]30,32,35,43], and 11 studies found no difference in PC between patients and controls (Table I, Supplementary Table VI) [11,15,28,29,33,37,41,42,44,46,47]. One study did not provide PC results.…”
Section: Pcmentioning
confidence: 99%
“…Increase in prothrombotic activity plays an important role in the developement of atherosclerosis [7]. In previous studies increase in MPV has been found to be related to cardiovascular and cerebrovascular diseases like hypertension, angina pectoris, myocardial infarction, and stroke [12][13][14][15]. In a different study it was concluded that increased MPV normalised with time in ischemic stroke patients and persistant increase was related to poor prognosis [16].…”
Section: Discussionmentioning
confidence: 99%